Global trends in the proportion of macrolide-resistant Mycobacterium Species: A systematic review and meta-analysis - Saeid Sadeghi Ghazi Chaki; Saeed Babaie Pirsoltan; Masoumeh Beig; Tahereh Navidifar; Elnaz Parvizi; Maryam Mofid; Narges Golab; Mohammad Sholeh (PLoS ONE, 2025)
Background Macrolide resistance in Mycobacterium species is an emerging global problem, complicating treating non-tuberculous mycobacteria (NTM) and Mycobacterium tuberculosis . Understanding global resistance patterns is essential to improve treatment strategies and reduce morbidity and mortality. Objective This study aimed to investigate macrolide resistance prevalence, distribution, and trends among Mycobacterium species in different world regions. Methods A comprehensive search of Scopus, PubMed, Web of Science, and EMBASE (2015–2023) assessed study quality using JBI guidelines. Resistance proportions were calculated with a random-effects model, and additional meta-regression and subgroup analyses explored variations and trends. Statistical analyses were conducted using R and the metafor package. Results Out of 5,718 records, 41 studies across 17 countries were included. Azithromycin resistance was reported in 17 reports (3 Studies), with 156 resistant isolates among 715 tested, yielding a pooled rate of 29.0% (95% CI: 19.5–40.7%). Clarithromycin resistance, assessed in 76 reports (40 Studies), included 1,071 resistant isolates among 3,923 tested, with a pooled rate of 30.5% (95% CI: 23.7–38.2%). Erythromycin resistance was reported in 17 reports (3 Studies), with 350 resistant isolates among 752 tested, giving a pooled rate of 50.3% (95% CI: 37.5–62.9%). Meta-regression revealed a significant upward trend in azithromycin resistance over time (r = 0.558, p = 0.005). Conclusion These findings underscore the need for targeted, region- and species-specific interventions to combat rising macrolide resistance in Mycobacterium species effectively.